2022
DOI: 10.1007/s00442-022-05212-w
|View full text |Cite
|
Sign up to set email alerts
|

Microclimatic conditions mediate the effect of deadwood and forest characteristics on a threatened beetle species, Tragosoma depsarium

Abstract: While climate change has increased the interest in the influence of microclimate on many organisms, species inhabiting deadwood have rarely been studied. Here, we explore how characteristics of forest stands and deadwood affect microclimate inside deadwood, and analyse how this affects wood-living organisms, exemplified by the red-listed beetle Tragosoma depsarium. Deadwood and forest variables explained much of the variation in temperature, but less of the variation in moisture within deadwood. Several variab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 52 publications
3
12
0
Order By: Relevance
“…Thus, our study together with some others (Paclik & Weidinger, 2007;Sedgeley, 2001;Wiebe, 2001) provide evidence that tree diameter is an important governor of the internal thermal conditions of hollows, but there are also studies that have found no relationship between tree diameter and microclimate (Clement & Castleberry, 2013;Coombs et al, 2010;Rhodes et al, 2009). That a larger diameter buffers temperature fluctuations has also been found for standing and downed deadwood (Lindman et al, 2022), probably because wood buffers the changes in temperature and moisture (Walczy nska & Kapusta, 2017). Many beetles that specialise on hollow trees occur more frequently in trees with larger diameters (Ranius & Jansson, 2000).…”
Section: Importance Of Tree Characteristics For Microclimatesupporting
confidence: 73%
See 4 more Smart Citations
“…Thus, our study together with some others (Paclik & Weidinger, 2007;Sedgeley, 2001;Wiebe, 2001) provide evidence that tree diameter is an important governor of the internal thermal conditions of hollows, but there are also studies that have found no relationship between tree diameter and microclimate (Clement & Castleberry, 2013;Coombs et al, 2010;Rhodes et al, 2009). That a larger diameter buffers temperature fluctuations has also been found for standing and downed deadwood (Lindman et al, 2022), probably because wood buffers the changes in temperature and moisture (Walczy nska & Kapusta, 2017). Many beetles that specialise on hollow trees occur more frequently in trees with larger diameters (Ranius & Jansson, 2000).…”
Section: Importance Of Tree Characteristics For Microclimatesupporting
confidence: 73%
“…O. eremita occurred more frequently in hollows with a warm and stable microclimate, that is, where the average temperature was higher in summer, and the temperature fluctuations in summer and moisture variation were lower. High temperatures and narrow temperature fluctuations have also been found to be important for other insects, for example, a moth (Moore et al, 2021), and a beetle: (Lindman et al, 2022) but we have not seen this documented for any insect species associated with tree hollows.…”
Section: Occurrence and Body Size Of O Eremitamentioning
confidence: 55%
See 3 more Smart Citations